2014
DOI: 10.1371/journal.pone.0096110
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Interventions for People Diagnosed with a Current Episode of an Anxiety or Depressive Disorder: A Meta-Analysis of Randomised Controlled Trials

Abstract: ObjectiveMindfulness-based interventions (MBIs) can reduce risk of depressive relapse for people with a history of recurrent depression who are currently well. However, the cognitive, affective and motivational features of depression and anxiety might render MBIs ineffective for people experiencing current symptoms. This paper presents a meta-analysis of randomised controlled trials (RCTs) of MBIs where participants met diagnostic criteria for a current episode of an anxiety or depressive disorder.MethodPost-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
258
6
17

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(306 citation statements)
references
References 49 publications
(82 reference statements)
17
258
6
17
Order By: Relevance
“…MBCT has been demonstrated to be effective in reducing relapse (Kuyken et al., 2016). In addition, it has been shown that MBCT reduces depressive symptoms in currently depressed patients (Strauss, Cavanagh, Oliver, & Pettman, 2014). Preliminary studies (Barnhofer Crane, Hargus, Amarasinghe, Winder, & Williams, 2009; Eisendrath et al., 2008; Kenny & Williams, 2007) have even found beneficial effects of MBCT for patients with chronic or treatment‐resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…MBCT has been demonstrated to be effective in reducing relapse (Kuyken et al., 2016). In addition, it has been shown that MBCT reduces depressive symptoms in currently depressed patients (Strauss, Cavanagh, Oliver, & Pettman, 2014). Preliminary studies (Barnhofer Crane, Hargus, Amarasinghe, Winder, & Williams, 2009; Eisendrath et al., 2008; Kenny & Williams, 2007) have even found beneficial effects of MBCT for patients with chronic or treatment‐resistant depression.…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing the above literature indicates that mindfulness has proven to be effective and beneficial for a range of problems as well for clinical as for non-clinical populations [3,11,12,17,21,32].…”
Section: The Present Studymentioning
confidence: 99%
“…Its mindfulness component may carry less stigma than conventional psychosocial interventions and it may prove to be of particular use in reducing risk for pre-and postpartum depression in pregnant women who prefer not to take medications. 25 Despite earlier misgivings, recent trials suggest that it also might be efficacious in the treatment of acute depression 26 and that it can be used to prevent the onset of depression in at least some at-risk adolescents. 27 However, again there have been difficulties delivering the approach effectively in everyday settings when delivered without clarity of training, delivery and supervision, and again short follow-up times for many studies has been an issue 28,29 .…”
Section: Mindfulness-based Cognitive Therapy (Mbct)mentioning
confidence: 99%